2011
DOI: 10.1371/journal.pone.0018252
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Pain Modulation Is Associated with Common Polymorphisms in the Serotonin Transporter Gene

Abstract: BackgroundVariation in the serotonin transporter (5-HTT) gene (SLC6A4) has been shown to influence a wide range of affective processes. Low 5-HTT gene-expression has also been suggested to increase the risk of chronic pain. Conditioned pain modulation (CPM) - i.e. ‘pain inhibits pain’ - is impaired in chronic pain states and, reciprocally, aberrations of CPM may predict the development of chronic pain. Therefore we hypothesized that a common variation in the SLC6A4 is associated with inter-individual variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 72 publications
(88 reference statements)
5
99
3
4
Order By: Relevance
“…However, no association between 5HTTLPR and the endophenotype, sensitivity to sensory stimuli, was observed. This is in contrast to another study that found that the S (low expressing) allele was associated with being less sensitive to heat, cold, and pressure pain compared with the L (high expressing allele) [45,46] in healthy individuals. FM patients are reported to be more sensitive to sensory stimuli, however, and the S allele was associated with an increased risk of FM in earlier studies [19].…”
Section: The Serotonergic Systemcontrasting
confidence: 99%
“…However, no association between 5HTTLPR and the endophenotype, sensitivity to sensory stimuli, was observed. This is in contrast to another study that found that the S (low expressing) allele was associated with being less sensitive to heat, cold, and pressure pain compared with the L (high expressing allele) [45,46] in healthy individuals. FM patients are reported to be more sensitive to sensory stimuli, however, and the S allele was associated with an increased risk of FM in earlier studies [19].…”
Section: The Serotonergic Systemcontrasting
confidence: 99%
“…35 This is relevant to serotonergic transmission because (1) individuals with low serotonin transporter gene expression, which facilitates serotonin reuptake from the synaptic cleft, have a tendency to focus on negative stimuli, and (2) polymorphisms in the serotonin transporter gene have been associated with alterations in pain scores and pain perception, including HP 0.5. 17,36,37 Similar to the PCS, greater PASS-20 scores were associated with lower standardized values of HP 0.5 and HP 5. This is consistent with previous studies where anxiety sensitivity was correlated with pain intensity and fear of pain.…”
Section: Discussionmentioning
confidence: 89%
“…A similar assumption has been proposed for children and adolescents (35), but the possibility that further mechanisms, such as instrumental learning (36) or learning by imitation (37), exist cannot be excluded. Furthermore, the contribution of genetic factors is likely but has only been shown in a few studies with adults so far (38)(39)(40).…”
Section: Are the Mechanisms Underlying The Placebo Effect Similar Betmentioning
confidence: 99%